2020
DOI: 10.1186/s12883-020-1614-x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased frontal white-matter diffusion and improved cognitive flexibility after burr-hole surgery in moyamoya angiopathy

Abstract: Background In Moyamoya Angioplasty (MMA), increased apparent diffusion coefficient (ADC) in frontal white matter (WM) with a normal appearance has been associated with frontal hypoperfusion and executive dysfunction. Multiple burr-hole surgery enables the revascularization of large frontal areas. Goal: To assess the effect of multiple burr-hole surgery on the ADC and cognitive functions in adults with MMA. Methods ADC was measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Previous studies reported mortality ranges between 0.86% [22] and 1.86% [23]. Overall adverse postoperative events (mainly ischemic and hemorrhagic stroke) are reported to be between 5-14% [22][23][24] in MMV, consistent with our results. Remarkably, the only randomized controlled surgical trial in MMD comparing STA-MCA bypass surgery to conservative treatment in adults who presented with hemorrhage reported not a single perioperative adverse event after 84 operations [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies reported mortality ranges between 0.86% [22] and 1.86% [23]. Overall adverse postoperative events (mainly ischemic and hemorrhagic stroke) are reported to be between 5-14% [22][23][24] in MMV, consistent with our results. Remarkably, the only randomized controlled surgical trial in MMD comparing STA-MCA bypass surgery to conservative treatment in adults who presented with hemorrhage reported not a single perioperative adverse event after 84 operations [25].…”
Section: Discussionsupporting
confidence: 92%
“…One Western study showed that-although there was no improvement in CVR-there was some improvement in executive functioning [24]. The difference in CVR change could be explained by the burr-hole technique used, possibly leading to a slower increase in hemodynamic functioning than the combined direct-indirect technique we used.…”
Section: Discussionmentioning
confidence: 91%
“…Multiple burr-hole surgery enables the revascularization of large frontal areas. In this sense, Calviere et al recently assessed the effect of such surgery on the ADC and cognitive functions in fourteen adults treated with angioplasty before and six months after the intervention [68]. ADC was obtained from regions of interest located in frontal and posterior (temporo-occipital) normal-appearing WM.…”
Section: Moyamoya Syndrome In Adults (Ammd)mentioning
confidence: 99%
“…Revascularization surgery in adult MMD changes cognitive function and prevents further cerebral ischemic events [ 6 , 11 , 12 , 13 , 14 , 15 ]. Most adult MMD patients who undergo revascularization surgery do not show cognitive changes relative to cognitive ability before surgery, although some patients do demonstrate improved or worsened cognitive function postoperatively [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies however repeated neuropsychological evaluation within 1 year after surgery [ 10 , 11 , 13 , 14 , 15 , 16 ]. Only 1 study performed neuropsychological testing >1 year but <2 years postoperatively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%